(untitled) (Journal of the College of Basic Education, 2025)
As a result of the increasing consumption of bottled drinking water in Iraq in general and Baghdad in particular and the recent increase in the number of factories producing this water, this research was prepared to evaluate the quality of drinking water and the output from factories. Where 55 samples of local bottled water, the most consumed in the city of Baghdad, were collected and examined from direct sales stations, taking into account the newness of the product, for the period from the last quarter of 2023 and the first quarter of 2024, at a rate of two samples for each sample. Some physical and chemical tests were conducted, namely the acid function (pH), dissolved solid salts (TDS), electrical conductivity (EC), and calculation of salinity concentration. All experiments were conducted at a temperature of 25 °C. The study aims to evaluate the quality of bottled water and its conformity with approved Iraqi specifications. The results of the study showed that most of the tests conformed to the requirements of the Iraqi specifications, with a difference between the specifications of the water produced and proven by the companies and the results of the practical tests, in addition to differences in the acid content of some companies from the standard specifications.